Clinical Presentation of Local Anesthetic Systemic Toxicity: A Review of Published Cases, 1979 to 2009. Issue 2 (1st February 2010) - Di Gregorio, Guido; Neal, Joseph M.; Rosenquist, Richard W.; Weinberg, Guy L.
Abstract : The classic description of local anesthetic systemic toxicity (LAST) generally described in textbooks includes a series of progressively worsening neurologic symptoms and signs occurring shortly after the injection of local anesthetic and paralleling progressive increases in blood local anesthetic concentration, culminating in seizures and coma. In extreme cases, signs of hemodynamic instability follow and can lead to cardiovascular collapse. To characterize the clinical spectrum of LAST and compare it to the classic picture described above, we reviewed published reports of LAST during a 30-year period from 1979 to 2009. Ninety-three cases were identified and analyzed with respect to onset of toxicity and the spectrum of signs and symptoms. Sixty percent of cases followed the classic pattern of presentation. However, in the remainder of cases, symptoms were substantially delayed after the injection of local anesthetic, or involved only signs of cardiovascular compromise, with no evidence of central nervous system toxicity. Although information gained from retrospective case review cannot establish incidence, outcomes, or comparative efficacies of treatment, it can improve awareness of the clinical spectrum of LAST and, theoretically, the diagnosis and treatment of affected patients. The analytic limitations of our method make a strong case for developing a prospective, global registry of LAST as a robust alternative for educating practitioners and optimizing management of LAST.